Bereaved - Knox, Ian (Eastbourne Kingsway Publications, 1994)
This title will help the bereaved to find a way through their time of grief and loss and will guide those who want to offer their comfort and support. Ian Knox tells of his own experiences and shares the stories of people who have suffered different kinds of bereavement. --This text refers to an out of print or unavailable edition of this title.
Include Appendix.
Keywords: Bereavement